1993
DOI: 10.1016/0735-1097(93)90405-p
|View full text |Cite
|
Sign up to set email alerts
|

Bedside cardiovascular examination in patients with severe chronic heart failure: Importance of rest or inducible jugular venous distension

Abstract: The bedside cardiovascular examination in the patient with chronic heart failure is extremely useful in identifying patients with elevation of right and left heart pressures. Examination for jugular venous distension at rest or by the abdominojugular test is simple and highly sensitive and specific in assessing left heart pressures in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(100 citation statements)
references
References 14 publications
2
94
0
4
Order By: Relevance
“…The presence of orthopnea and paroxysmal nocturnal dyspnea (PND) are two hallmark symptoms associated with the diagnosis of fl uid overload secondary to AHF. When evaluated more closely in a study of 52 patients with established left ventricular dysfunction, Butman et al (8) showed that only 50 % presented with orthopnea and 35 % with PND. In a meta-analysis of over 22 studies on the diagnosis of CHF performed by Wang et al (9) it was shown that the pooled sensitivities and specifi cities of common symptoms between the studies yielded only modest values for the diagnosis or exclusion of HF.…”
Section: History Assessmentmentioning
confidence: 99%
“…The presence of orthopnea and paroxysmal nocturnal dyspnea (PND) are two hallmark symptoms associated with the diagnosis of fl uid overload secondary to AHF. When evaluated more closely in a study of 52 patients with established left ventricular dysfunction, Butman et al (8) showed that only 50 % presented with orthopnea and 35 % with PND. In a meta-analysis of over 22 studies on the diagnosis of CHF performed by Wang et al (9) it was shown that the pooled sensitivities and specifi cities of common symptoms between the studies yielded only modest values for the diagnosis or exclusion of HF.…”
Section: History Assessmentmentioning
confidence: 99%
“…The value of symptoms and signs in the diagnosis of CHF has rarely been tested in large numbers of patients representative of those found in the community [2][3][4][5][6][7][8]. Most studies have investigated hospital populations (in-or outpatient referrals), which are a selected group with more severe CHF [2][3][4][5][6][7], a problem identified by the authors.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have investigated hospital populations (in-or outpatient referrals), which are a selected group with more severe CHF [2][3][4][5][6][7], a problem identified by the authors. The accuracy of clinical diagnosis found in those studies should not be generalized to the whole population.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Emerging data on serum measurement of B-type natriuretic peptide (BNP), a hormone secreted mainly by the left ventricular (LV) myocardium in CHF, show promise that it may be an important aid to physicians in identifying patients with heart failure and defining outcomes. Levels of BNP may be used as a surrogate marker of decreased ventricular function and increased ventricular filling pressures 7,8 and compare favorably with other surrogate markers of CHF prognosis, such as plasma renin activity and serum norepinephrine.…”
Section: Introductionmentioning
confidence: 99%